Wireless sensor network deployment performance based on FOA, PSO and TPSMA / Nurhidayah Kamal Akbar, Husna Zainol Abidin, and Ahmad Ihsan Mohd Yassin - Kamal Akbar, Nurhidayah; Zainol Abidin, Husna; Mohd Yassin, Ahmad Ihsan (Universiti Teknologi MARA, 2019)
One of the crucial challenges in deploying a Wireless Sensor Network (WSN) is the position of the sensor nodes. It may create coverage holes as the sensor nodes become redundant for each distribution. These coverage holes emerge when some of the points in terrain area is not covered by any sensor nodes. Hence, sensor node full connectivity may not be achieved and energy consumption will be increased in sensing and communicating due to the distance between the sensor nodes. This paper compares the random deployment with other two algorithms known as Fruit Fly Optimization (FOA) and Particles Swarm Optimization (PSO) Territorial Predator Scent Marking Algorithm (TPSMA) to solve the coverage hole problem. The performance of these algorithms are compared in terms of coverage, connectivity and energy consumption. A performance study was carried out using MATLAB and Network Simulator 2 (NS2) on Linux platform. Based on the simulation work that have been done, it can been seen that FOA outperforms PSO, TPSMA and random deployment.